Three-dimensional Finite Element Analysis of the Senise Landslide. (2016) - Troncone, Antonello; Conte, Enrico; Donato, Antonio
Abstract: The results of a three-dimensional (3D) analysis concerning the Senise landslide are presented. This landslide occurred after deep excavations had been carried out at the toe of the slope for constructing several buildings. The soils involved in the landslide were characterized by a pronounced strain-softening behaviour. The analysis is performed using a finite element approach in which an elasto-viscoplastic constitutive model is incorporated. The strain-softening behaviour of the soils is simulated reducing the strength parameters from peak to residual, with the accumulated deviatoric plastic strain. The results from this analysis account for the occurrence of a 3D progressive failure process in the slope.